Enhanced dissolution and oral bioavailability of valsartan solid dispersions prepared by a freeze-drying technique using hydrophilic polymers. (2nd January 2016) - Xu, Wei-Juan; Xie, Hong-Juan; Cao, Qing-Ri; Shi, Li-Li; Cao, Yue; Zhu, Xiao-Yin; Cui, Jing-Hao
Abstract: This study aimed to improve the dissolution rate and oral bioavailability of valsartan (VAL), a poorly soluble drug using solid dispersions (SDs). The SDs were prepared by a freeze-drying technique with polyethylene glycol 6000 (PEG6000) and hydroxypropylmethylcellulose (HPMC 100KV) as hydrophilic polymers, sodium hydroxide (NaOH) as an alkalizer, and poloxamer 188 as a surfactant without using any organic solvents. In vitro dissolution rate and physicochemical properties of the SDs were characterized using the USP paddle method, differential scanning calorimetry (DSC), X-ray diffractometry (XRD) and Fourier transform-infrared (FT-IR) spectroscopy, respectively. In addition, the oral bioavailability of SDs in rats was evaluated by using VAL (pure drug) as a reference. The dissolution rates of the SDs were significantly improved at pH 1.2 and pH 6.8 compared to those of the pure drug. The results from DSC, XRD showed that VAL was molecularly dispersed in the SDs as an amorphous form. The FT-IR results suggested that intermolecular hydrogen bonding had formed between VAL and its carriers. The SDs exhibited significantly higher values of AUC0–24 h and C max in comparison with the pure drug. In conclusion, hydrophilic polymer-based SDs prepared by a freeze-drying technique can be a promising method to enhance dissolution rate and oral bioavailability of VAL.